Sex differences of neural connectivity in internet gaming disorder and its association with sleep quality: an exploratory fMRI study - Zhou, Mingzhe; Gao, Guoqing; Rong, Bei; Zhao, Haomian; Huang, Junhua; Tu, Ning; Bu, Lihong; Xiao, Ling; Wang, Gaohua (Frontiers in Psychiatry, 2024)
Sex-specific differences in internet gaming disorder (IGD) neurophysiology remain underexplored.Here we investigated sex-related variability in regional homogeneity (ReHo) and functional connectivity (FC) in IGD and their correlations with sleep quality. Resting-state functional magnetic resonance imaging (fMRI) scans were performed on 52 subjects with IGD and 50 healthy controls (HCs). Two-way ANOVA was used to examine sex and diagnosis interactions in ReHo and FC, followed by post-hoc analyses to explore FC biomarkers for different sexes. In ReHo analysis, the four groups showed significant sex and diagnosis interactions in the right middle frontal gyrus (rMFG). FC analysis with rMFG as the seed region revealed a significant sex and diagnosis interaction effect in FC of the rMFG with the bilateral postcentral gyrus (PoCG). In male IGD group, FC between the rMFG and the bilateral PoCG correlates strongly with daytime dysfunction score and the Pittsburgh sleep quality inventory (PSQI) total score. These findings emphasize the importance of considering sexual dimorphism in the neurobiology of IGD, which might influence subsequent treatment strategies.